HOW BRAND TRUST CAN MEDIATE ELECTRONIC WORD-OF-MOUTH AND INFORMATION CREDIBILITY ON PURCHASE INTENTION - Ardana, Defan; Laili Fikriah, Nur (Universitas Islam Lamongan, 2025)
Mie Gacoan, a popular noodle restaurant in Indonesia, is known for its spicy noodles of various levels and innovative marketing strategies, attracting the attention of consumers, especially young people. This study analyzes the influence of Electronic Word-of-Mouth (eWOM) and information credibility on consumer purchase intention, with brand trust as a mediating variable. The study was conducted at Mie Gacoan, Malang City using a quantitative descriptive method. The sample consisted of 150 respondents selected through purposive sampling, with primary data obtained through a Likert-based questionnaire and secondary data from the literature. Data analysis using PLS with SmartPLS 4.0 includes validity, reliability, and relationship tests between variables. The results of the study indicate that eWOM and information credibility have a significant effect on brand trust, which in turn increases consumer purchase intention. In addition, both variables also have a direct effect on purchase intention. Brand trust is proven to be a mediator that strengthens the relationship between eWOM and purchase intention, emphasizing the importance of brand trust in consumer decision making.